Produksi Enzim Selulase olehAspergillus niger pada Ampas Sagu - Idiawati, Nora; Harfinda, Elliska Murni; Arianie, Lucy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2014)
Production of cellulase by Aspergillus niger was carried out by growing the cultureson sago waste. Sago waste containscellulose that has not been used optimally. Cellulose is a polysaccharide consisting of glucose monomers linked by β-1,4-glycosides bonds. Glycoside bonds in cellulose can be enzymatically hydrolyzed into glucose with cellulase enzymes. Solid fermentation used to produce cellulase on sago waste as substrate was influenced by pH (3 to 6), moisture content(40% to 85%), and fermentation time (4 to 10 days). Products of the cellulase enzyme activity was measured by phenolsulfuricacid method. The results showed that the highest cellulase enzyme activity was 0.172 U/mL obtained at 85%moisture content, pH 5, and 8 days of fermentation time.